China's modern economy in historical perspective : sponsored by the Social Science Research Council - Perkins, Dwight H.; Zhao, Gang; Social Science Research Council (U.S.) (Stanford, Calif. : Stanford University Press, 1975)
Why did it take China more than a century after its defeat in the first Opium War to begin acquiring the fruits of modern technology? To what extent did the rapid economic developments after 1949 depend on features unique to China and to Chinese history and on the socialist reorganization of society? This book deals with these questions.
Revised papers from a conference held in Bermuda in June 1973 under the sponsorship of the Subcommittee for Research on the Chinese Economy of the Joint Committee on Contemporary China of the Social Science Research Council and the American Council of Learned Societies.
Includes bibliographical reference and index
aia 17/10/2018
Keywords: Economic development; China; China